Useful City or the truth about systemic context of depopulation and shrinking cities - Jacek Kaczmarek; Adam Dąbrowski (Rozwój Regionalny i Polityka Regionalna)
In recent years, the phenomenon of depopulation and shrinkage of cities has been observed. The depopulation of large cities is undoubtedly a demographic fact. The process of urban depopulation has recently become the theme of numerous reports and alarmist research works. However, it can be concluded that the diagnostic background of this phenomenon has got a narrow methodical foundation. As a measure of depopulation, the number of permanent residents is usually taken (according to the place of residence). Thus, the diversity, complexity and dynamics of processes taking place in contemporary cities are ignored. Postmodern reality appears as a segregated, separated world. Therefore, the diagnostic approaches currently used should be discussed. Going further, one can conclude that the measurement of depopulation and shrinkage of cities by the number of permanent residents is a simplification, because it ignores the essence of urbanity, which is the diversity of values offered by the urban space of exchange (i.e. the utility value). The article presents therefore the new concept of the measurement for shrinking of cities. Ideas discussed in the paper are expected to stimulate critical exchange of views among urban researchers. In the authors’ opinion, the sin of social-economic geography and spatial economics consists in boiling down great human affairs to aspects of correct representativeness.